GENETIC POLYMORHISM OF CASPASE 8 AND 9 IN IRAQ - Abdullah , Duaa; Aloubaidy, Reema M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study examined the potential association between polymorphisms of Caspase 9 −293del (rs4645982) and Caspase8−652 6N ins / del (rs3834129) and the danger of acute and chronic myeloid leukaemia in Iraqi population. This case-control study was conducted as 128 (62 acute, and 66 chronic) myeloid leukaemia patient and 65 healthy individuals not infected with cancer. A conventional PCR method was used for detection in this study. The results showed that the Caspase9 −293del (rs4645982) in homozygous and heterozygous deletion genotypes were associated significantly with CML risk (  p=  0.001  and   0.005 ,respectively ) and in homozygous insertion and deletion genotypes of Caspase 8 -652 6N were also associated significantly with CML risk (p= 0.004  and p= 0.00, respectively), while there were non significant association between Caspase9 −293del (rs4645982) and  Caspase8 −652 6N (rs3834129) with AML risk in all genotypes of them  p > 0.05. These findings suggest that polymorphisms in the Caspase-9 and Caspase-8 genes might be useful markers for determining genetic susceptibility to CML and AML. The results of this study suggest that Caspase9-293  is associated with increased risk of CML in case of  homozygous of deletion, and insertion  in case of AML, while in  Caspase8-652 6N insertion  polymorphism are associated with increased risk of  both CML and AML in a sample of Iraqi populations.